Hubungan Peran Orang Tua dalam Pelaksanaan Family Centered Care (FCC) dengan Tingkat Kecemasan Anak Usia Prasekolah (3-6 Tahun) yang Mengalami Hospitalisasi di Ruang Anak Rsia Muslimat Jombang - Robiatul Rohmaniah; Pujiani; Andi Yudianto; Zuliani; Ana Farida Ulfa (Indo Publishing, 2026)
The role of parents is needed to minimize the causes of anxiety and reduce the impact of separation as well as as partners for nurses to determine the fulfillment of children's needs in the form of family-centered nursing care called Family Centered Care (FCC), family-centered care has proven to be beneficial for patients. The aim of this research is to determine the relationship between the role of parents in implementing family centered care (FCC) and the anxiety level of preschool aged children (3-6 years) who are hospitalized in the children's room at RSIA Muslimat Jombang. The research design used was Cross Sectional and Purposive Sampling techniques. The population in this study were parents of patients who had preschool age children (3-6 years) who were treated in the Children's Room at RSIA Muslimat Jombang. The sample in this study consisted of 75 respondents who met the inclusion and exclusion criteria. By using the Family Cantered Care (FCC) questionnaire and the Spence Children's Anxiety Scale Preschool (SCAS) anxiety scale questionnaire. The results of the Spearman Rank test obtained P Value: 0.01 (α = 0.05), meaning there is a relationship between the role of parents in implementing family centered care (FCC) and the anxiety level of pre-school age children (3-6 years) who are hospitalized in the hospital. children of RSIA Muslimat Jombang. The better the role of parents, the greater the possibility of minimizing the anxiety level of preschool aged children when undergoing hospitalization. It is recommended that parents always accompany their children when they are hospitalized in order to minimize the causes of anxiety by reducing the impact of separation, preventing feelings of loss of control and minimizing fear of pain.